Variants in MME are associated with autosomal‐recessive distal hereditary motor neuropathy. Issue 9 (20th August 2019) - Hong, Daojun; Fang, Pu; Yao, Sheng; Chen, Juanjuan; Zhang, Xiaolei; Chen, Shuyun; Zhang, Jingfen; Tan, Dandan; Wang, Li; Han, Xinsheng; Xin, Ling; Wang, Yan; et al.
Abstract: Objective: To identify a new genetic cause in patients segregating distal hereditary motor neuropathy (dHMN) with an autosomal recessive pattern. Methods: Whole‐exome sequencing was conducted in two siblings and was combined with segregation analysis. Additionally, 83 unrelated dHMN patients with unknown genetic cause were screened. RNA analysis was performed using blood lymphocytes and HEK293 cells transfected with mutant plasmids. Immunohistochemistry and Western blot analysis was applied to the nerve tissue. The enzymatic activities of mutant proteins were measured in the cultured cells to verify the pathogenicity of variants. Results: The clinical features of the patients showed late‐onset phenotype of distal motor neuropathy without sensory involvement. We identified that compound heterozygous variants of c.1342C>T and c.2071_2072delGCinsTT in the membrane metalloendopeptidase (MME) gene co‐segregated with the phenotype in a dHMN family. In an additional group of 83 patients with dHMN, compound heterozygous variants of c.1416+2T>C and c.2027C>T in MME were identified in one patient. The splice site variant c.1416+2T>C results in skipping of exon 13. The stop variant c.1342C>T induces mRNA degradation via nonsense‐mediated mRNA decay. Transcript levels of MME in the lymphocytes showed no significant differences between the patients and controls. We also identified that MME variants were associated with mild decrease in protein expression in the sural nerve and significant impairments of enzymatic activity. Interpretation: Variants in the MME gene were associated with not only a Charcot‐Marie‐Tooth neuropathy phenotype but also with an autosomal‐recessive dHMN phenotype. Loss of function may play a role in the pathogenesis of dHMN.